Symptoms of functional disorders of the stomatognathic system among students - Odzimek, Martyna (Journal of Education, Health and Sport, 2022)
INTRODUCTION The stomatognathic system is a morphological and functional group of tissues and organs, the main task of which is food intake, initial chewing and digestion, but also emotional expression, speech articulation and breathing. Dysfunctions in the masticatory system may take the form of: muscle or joint pain, excessive muscle tension, crackles in the temporomandibular joints and reduced mobility, tooth clenching or ear ailments, especially in the form of: noise, hypersensitivity or deterioration of hearing. OBJECTIVE The main aim of the study was to assess the occurrence of functional dysfunctions of the stomatognathic system among students. The research was carried out from January to February 2022 using the proprietary online questionnaire and the results were statistically analyzed using the chi-square test. RESULTS There was a statistically significant relationship (p≤0,05) between the occurrence of stomatognathic system disorders and the location of the headache (rc = 0,0252 – weak strength of the relationship), muscle tension (rc = 0,304 - average strength of the relationship) and ear ailments (rc = 0,35 - average strength of the relationship). CONCLUSIONS The most important issue in the treatment of stomatognathic system disorders is the interdisciplinary and holistic view of the patient. It is important to introduce multidirectional and multi-stage therapy, thanks to which we can achieve maximum therapeutic effects.